Stainless steels for bioprocessing - Dillon, C. P.; Rahoi, D. W.; Tuthill, A. H. (Nickel Development Institute, 1994)
This article describes the characteristics of stainless steels, some criteria for the selection of materials for process equipment, the basics of corrosion and corrosion control, and some principles of quality assurance for the procurement of stainless steel equipment.
"Based on a four-part series published in Biopharm, Volume 5, 1992"
Keywords: Stainless steel.; Biochemical engineering.; elektronické knihy; electronic books